1997
DOI: 10.1063/1.118746
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of leakage currents of Pt/(Ba, Sr)TiO3/Pt capacitors

Abstract: Pt/(Ba, Sr)TiO 3 /Pt capacitors fabricated by sputtering technique showed abnormally higher leakage current when negative bias was applied to the top electrode. In this letter, two kinds of processes were attempted to reduce high leakage current of Pt/BST/Pt capacitors for dynamic random access memory devices: (1) postannealing under O2 atmosphere and (2) adding oxygen into sputtering gas of platinum top electrode. These processes were very effective to reduce the oxygen vacancy in the BST films which are most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…12,13 Therefore, it is considered that the oxygen vacancy effect on barrier height can be obtained by calculating the difference of the Schottky barrier height of the B 5 N 3 films grown under low (1.7 mTorr) and high (5.1 mTorr) OPPs. The leakage current density (J) due to the Schottky emission is expressed by the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Therefore, it is considered that the oxygen vacancy effect on barrier height can be obtained by calculating the difference of the Schottky barrier height of the B 5 N 3 films grown under low (1.7 mTorr) and high (5.1 mTorr) OPPs. The leakage current density (J) due to the Schottky emission is expressed by the following equation:…”
Section: Resultsmentioning
confidence: 99%
“…Nd or Eu instead of La) leads to and off-stoichiometry that could involve oxygen losses, which can be induced during the processing [14,30,31]. It was reported that the leakage current of oxide films could be reduced by activated oxygen annealing [39]. Considering these results, and in order to evidence an effect of oxygen vacancies, the BNdFN film was ex-situ annealed under oxygen atmosphere at the deposition temperature.…”
Section: Dielectric Characterization Of Ba 2 Lnfenb 4 O 15 Thin Filmsmentioning
confidence: 97%
“…8 Many researches have reported the effect of the postannealing treatment under an O 2 and/or N 2 atmosphere in the behavior of BST film leakage currents. Joo et al 6 have reported oxygen vacancies in BST films, obtained by the sputtering technique, that are usually generated during the production of Pt/BST/Pt capacitors. These vacancies are responsible for the higher leakage currents of BST films, as well as for the degradation of dielectric properties.…”
mentioning
confidence: 99%